Kualitas Pelayanan Digital Dan Keputusan Pembelian pada Studi Kasus Cafetaria Labbis-Polban, Bandung, Indonesia - Tia Monica, Syalsabila; Triyanto, Fajar Akhmad (Asosiasi Ahli Administrasi Indonesia, 2025)
This study aims to analyze the impact of virtual service quality on consumer purchasing decisions at Cafeteria Labbis POLBAN. In an era of interconnected digital technology, consumers increasingly rely on digital platforms to make purchasing decisions, including when selecting dining options. Digital service quality, encompassing reliability, security, accessibility, responsiveness, and personalization, is pivotal in enhancing consumer satisfaction and loyalty. This research adopts a quantitative approach utilizing a descriptive causal method and employs multiple linear regression analysis to examine the impact of digital service quality on purchasing decisions. The findings indicate that digital service quality significantly influences purchasing decisions at Cafeteria Labbis, with reliability and responsiveness emerging as the most dominant elements. Additionally, high-quality digital services contribute to increased customer loyalty. Based on these findings, it is recommended that Cafeteria Labbis continue to enhance its digital service quality by improving device reliability, ensuring transaction security, and increasing responsiveness to customer needs, thereby strengthening the customer experience and encouraging repeat purchases.